Fiziologiceskie aspekty olimpijskich edinoborstv (obzor literatury) - Aranson, M. V.; Ozolin, E. S.; Tuponogova, O. V.; Shustin, B. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
An analysis of foreign scientific literature devoted to the physiological characteristics of athletes in the Greco-Roman wrestling, taekwondo and fencing was conducted. The main research is devoted to the study of the physiological response to training effects. In addition, the relationship between physiological indicators and performance, as well as testing equipment use, is considered. Interrelations between age, competition level and physiological determinants are studied. Researchers pay attention to the importance of motor reactions for optimal performance. The subject of research is closely related to the specifics of competitive activities in these types of martial arts.